Evolution and multivariable analysis of trace elements in groundwater of an agricultural area in a semi-arid region of Mexico. (October 2018) - Mora, Abrahan; Mahlknecht, Jürgen; Torres-Martínez, Antonio
Abstract: The evolution of several trace elements was evaluated in shallow groundwater of an agricultural area located in a semi-arid region of northeastern Mexico. A Principal Component Analysis (PCA) was performed to assess the geochemical processes controlling the distribution and mobility of these elements. Five principal components (PC) were significant. PC1 indicates that Ti and Si come from soil/silicate weathering. Sulfate, Mo and U were grouped in PC2, indicating the same redox behavior. PC3 shows similar sources for Rb and Cs (halite weathering), whereas the PC4 grouped the immobile elements Cd and Pb. The correlation found between Zn and Cu in PC5 indicates a similar behavior of both elements during the weathering and transport. Although the measured trace elements were detected in groundwater, their concentrations were lower than the guidelines values for safe drinking water proposed by international organizations, suggesting that these elements do not pose any significant threat to consumers.